Infant Mortality from Scabies Complicated by Sepsis and Renal Failure–A Case Report in Twin Infants at a Government Hospital in Benin City, Edo State, Nigeria - I. G. Enato; A. E. Sokunbi (Journal of Applied Sciences and Environmental Management)
Scabies remains a common parasitic infestation associated with poor living conditions and overcrowding which is caused by the sarcoptes scabies mite; and mostly affects those in extremes of age. This paper therefore evaluates Infant Mortality from Scabies Complicated by Sepsis and Renal Failure in Twin Infants at a Government Hospital in Benin City, Edo State, Nigeria using appropriate clinical and standard methods such as papules which can be scaly, presence of burrows, intense nocturnal pruritus and irritability; and excoriations on the skin which can serve as a portal for infection. Although Scabies is considered to be benign; it can however be complicated in rare case with overwhelming bacterial infection leading to septicaemia and renal compromise especially in children; and this requires prompt diagnosis and treatment.  We report a case of scabies complicated by overwhelming sepsis in twin infants arising from delay in seeking care and impeded diagnosis due to atypical presentation from possible associated abuse of super-potent steroids in Twin infants; eventually resulting in the mortality of one of the Twin. Availability of proper diagnostic measures and tools; along with appropriate treatment is essential for scabies cases to prevent attendant complications. Abuse of triple action creams should be discouraged and its availability restricted due to the far-reaching implications of its use and complications.